Prediction of major complications after hepatectomy using liver stiffness values determined by magnetic resonance elastography. Issue 9 (23rd April 2018) - Sato, N; Kenjo, A; Kimura, T; Okada, R; Ishigame, T; Kofunato, Y; Shimura, T; Abe, K; Ohira, H; Marubashi, S
Abstract: Background: Liver fibrosis is a risk factor for hepatectomy but cannot be determined accurately before hepatectomy because diagnostic procedures are too invasive. Magnetic resonance elastography (MRE) can determine liver stiffness (LS), a surrogate marker for assessing liver fibrosis, non-invasively. The aim of this study was to investigate whether the LS value determined by MRE is predictive of major complications after hepatectomy. Methods: This prospective study enrolled consecutive patients who underwent hepatic resection between April 2013 and August 2016. LS values were measured by imaging shear waves by MRE in the liver before hepatectomy. The primary endpoint was major complications, defined as Clavien–Dindo grade IIIa or above. Logistic regression analysis identified independent predictive factors, from which a logistic model to estimate the probability of major complications was constructed. Results: A total of 96 patients were included in the study. Major complications were observed in 15 patients (16 per cent). Multivariable logistic analysis confirmed that higher LS value ( P = 0·021) and serum albumin level ( P = 0·009) were independent predictive factors for major complications after hepatectomy. Receiver operating characteristic (ROC) analysis showed that the best LS cut-off value was 4·3 kPa for detecting major complications, comparable to liver fibrosis grade F4, with a sensitivity of 80 per cent and specificity of 82 per cent. A logistic model using the LS value and serum albumin level to estimate the probability of major complications was constructed; the area under the ROC curve for predicting major complications was 0·84. Conclusion: The LS value determined by MRE in patients undergoing hepatectomy was an independent predictive factor for major complications. Abstract : Liver stiffness predicts complications